Consumerism in Digital Age: A Sociological Exploration of Consumption Relations in Kathmandu - K.C., Arjun (Kutumbha vani, 2025)
The consumption behaviors in the urban environment like Kathmandu have changed in the digital age due to the impact of socio-cultural, economic, and demographic forces. The study examines the consumption patterns of residents of Ward No. 16 of Kathmandu Metropolitan City through a mixed-method study. Both quantitative and qualitative data of conducted structured surveys and in-depth interviews show that there is a dynamic consumer environment where both traditional and modern trends co-exist. The economic differences greatly determine the choices of purchases, where the high-income households prefer high-quality products and online shopping, whereas low-income families are inclined to the purchases of essential products in the local markets. The level of education turns out to be one of the most important factors of digital shopping, which shows a digital gap. Consumption is still shaped by cultural practices particularly at festivals. The research highlights the intricacies of the consumer behavior in the cities and how digital shopping is increasingly becoming popular among younger and more educated generations. The findings offer useful information to policy makers and companies intending to meet the varied consumer demands, advance digital accessibility and establish culturally adaptable marketing strategies. This discussion can be linked to the general discussion of the sociology of urban areas as it places the global consumer trends in the local context of Kathmandu.